Escaping the Crash? The Protective Power of Liquidity in the Pakistan Stock Market - Saleem, Sana; Usman, Muhammad; Rafique, Amna (The Indonesian Capital Market Review, 2026)
This study investigates the effect of stock liquidity on the risk of stock price crashes, taking sample of non-financial firms listed on the Pakistan Stock Exchange, from 2009 to 2024. A two-step system GMM estimation is applied to test the hypotheses. The results reveal that greater stock liquidity significantly reduces crash risk, whereas illiquidity amplifies it. Two underlying channels explain this relationship; first, liquidity strengthens block holders’ capacity to intervene, discouraging managerial tendencies to withhold adverse information, second, liquidity enhances price informativeness, limiting managerial discretion to manipulate prices through delayed disclosure of bad news. The findings imply that liquid stocks not only improve internal governance but also contribute to market stability. These insights support regulatory measures aimed at fostering liquidity, as a means of mitigating extreme downside risks in equity markets.